Performance demands of professional male tennis players - Johnson, C D (BMJ Group, 2006)
OBJECTIVE: To quantify the performance demands in professional male tennis. METHODS: Games from three grand slam tournaments were analysed by an elite tennis player from video recordings. Game related data were collected on 22 players (French Open, 8 (186 games); Wimbledon, 11 (206 games); US Open, 9 (224 games)). Total number of strokes per game was quantified separately for service and return games. Strokes were categorised by type and designated as forehand or backhand. Differences in the types of strokes in a game were analysed using one factor (type of stroke) repeated measures analysis of variance. Differences in total strokes and stroke distributions between playing surfaces were analysed by analysis of variance (surface type) with Tukey's post hoc pairwise comparisons. RESULTS: For service games there were more serves per game than any other type of stroke (p<0.001), with topspin forehand and topspin backhand the only other strokes averaging more than one per service game. For return games there were more forehand and backhand returns and topspin forehands and backhands than other types of stroke (p<0.01). Total number of strokes per game was greater in the French Open than Wimbledon (p<0.01), with more topspin forehands (p<0.01) and more topspin backhands (p<0.01). Total strokes per game in the US Open were not different from the other two tournaments. CONCLUSIONS: The serve was the predominant stroke accounting for 45% (French Open) to 60% (Wimbledon) of strokes during service games. The greater number of strokes per game on clay v grass may contribute to earlier fatigue.